Population Pharmacokinetics and Exposure–Response of Luspatercept, an Erythroid Maturation Agent, in Anemic Patients With Myelodysplastic Syndromes. (30th June 2020) - Chen, Nianhang; Kassir, Nastya; Laadem, Abderrahmane; Maxwell, Stephen E.; Sriraman, Priya; Giuseppi, Ana Carolina; Ritland, Steve; Linde, Peter G.; Budda, Balasubrahmanyam; Reynolds, Joseph G.; Zhou, Simon; Palmisano, Maria
Abstract : Luspatercept is a recombinant fusion protein that enhances late‐stage erythroid maturation. This report describes the population pharmacokinetics and exposure–response relationship of luspatercept in 260 patients with anemia due to myelodysplastic syndromes. Luspatercept displayed linear and time‐invariant pharmacokinetics over a dose range of 0.125–1.75 mg/kg administered subcutaneously once every 3 weeks. Body weight was the only clinically relevant covariate of luspatercept exposure, supporting the weight‐based dosing. The probability of achieving transfusion independence ≥ 8 weeks increased with time‐averaged luspatercept serum exposure, reaching the plateau at doses 1.0–1.75 mg/kg. The probability of achieving multiple efficacy end points increased with slower luspatercept clearance, independent of effects of luspatercept exposure or disease characteristics. The probability of experiencing severe treatment‐emergent adverse events decreased with increasing luspatercept exposure, especially during long‐term treatment. These results provide a positive benefit–risk profile for the titration‐to‐response dose regimen (1.0–1.75 mg/kg) recommended for this population.